The Students’ Ability in Using Lexical Collocation In Sentences at State Islamic University of North Sumatra - Iris April L Ramirez (XXXXXXXX, 2023)
ABSTRACT. To enable pre-service teachers acquire the certain teaching skills, well-planned educational programs and well-trained teachers are needed to implement these programs. Indeed, teacher education institution hold a major responsibility in training qualified pre-service teachers as it is essential for the welfare of a country and securing the quality of all educational levels from primary to tertiary education. To determine the level of teaching skills, a qualitative descriptive method was used with 96 pre-service teachers. The study adopted and modified a scale according to the needs of the study and validated by experts. The present study found that the pre-service teachers of BukSU generally are prepared for classroom work as revealed  in  the  results of their  internship in the laboratory school as well as during their off-campus which  consists  of  their  roles  as  student interns and  their  ability  to  handle  students’  participation. Qualitative research methods can be resorted to in order to perform in-depth descriptive studies to investigate the differences in the teaching skills of pre-service teachers from different indicators.Keywords: pre-service teachers, teaching, skills, teacher education, internship